Correlation Study of Cotinine and Monocyte Chemoattractant Protein-1 (MCP-1) with Carotid Intima-Media Thickness (cIMT) in Male Active Tobacco Smoke - Satwikajati, Sawitri; Kurnianingsih, Novi; Tjahjono, Cholid Tri; Wihastuti, Titin Andri; Sargowo, Djanggan; Rizal, Ardian (Universitas Brawijaya, 2024)
Background : Tobacco smoke exposure induces intima-media thickness by reducing nitric oxide and increasing adhesive molecule activity, with circulating cotinine serving as a marker; we hypothesize a correlation between monocyte chemoattractant protein-1 (MCP-1) and carotid intima-media thickness (cIMT) in active male smokers. Method : We conducted an observational cross-sectional analytic study involving 125 male participants, with 62 being active tobacco smokers and 63 non-smokers. Data were presented as mean ± SD, and the correlation between variables was analyzed using Pearson correlation. Result : Cotinine and MCP-1 levels were significantly higher in the smoker population (p 0.000) compared to non-smokers. The incidence of positive cIMT findings was higher in the smoker group (5%) than in the non-smoker group (2%). In the active smoker population, cotinine (r 0.21; p 0.11) showed a positive but non-significant correlation with positive cIMT findings, while MCP-1 showed a negative correlation (r -0.19, p 0.14) with positive cIMT findings. Smoking duration (r 0.162; p 0.223) and the amount of tobacco smoke (r 0.003; p 0.982) demonstrated a positive correlation with cotinine. MCP-1 exhibited a non-significant positive correlation with smoking duration (r 0.122; p 0.345) and a non-significant negative correlation with the amount of tobacco smoke (r -0.002; p 0.989). Conclusion : Among active tobacco smokers, cotinine showed a positive but non-significant correlation with positive cIMT findings, while MCP-1 exhibited a non-significant negative correlation with positive cIMT findings.